Robotic automated fiber placement of carbon fiber towpregs. Issue 5 (4th April 2022) - Forcellese, A.; Mancia, T.; Russo, A.C.; Simoncini, M.; Vita, A.
ABSTRACT: Robotic Automated Fiber Placement (R-AFP) technology was developed to manufacture composite laminates by placing carbon ﬁber thermoset towpregs, obtained by impregnating 12 K high-strength grade carbon fibers in an epoxy resin system. In order to avoid placement induced defects, a thermographic scanning technique was implemented for on-line quality monitoring of the R-AFP process. The thermal analysis proved to be an effective and quick approach for the real-time detection of deposition defects generated during. The R-AFP process was performed by applying a constant pressure through the compaction roller; different pressure values were investigated. The effect of the resin weight fraction and compaction pressure on the mechanical properties applied by the deposition head during R-AFP of cross-ply laminates was studied. The reduction of the tensile strength and the increase of the elastic modulus with decreasing pressure of the compaction roller was observed. Furthermore, the values of ultimate tensile strength and elastic modulus decrease as the resin content increases. Finally, the three-dimensional topography of surface fracture of tensile samples was investigated by means of the optical and scanning electron microscopy.